Analisis Penggunaan Bank Digital Berbasis Sistem Informasi Akuntansi Menggunakan Model UTAUT2 pada Generasi Z di Kota Bandar Lampung - Indy Basitu Rahma; Agrianti Komalasari (International Forum of Researchers and Lecturers, 2025)
This study aims to evaluate the factors influencing the adoption of digital banking among Generation Z in Bandar Lampung using the UTAUT2 model. The research employs a quantitative approach, with purposive sampling as the sampling technique. Data analysis is conducted using SmartPLS 4.0 with the PLS-SEM method. Primary data for this study was collected through an online survey via Google Forms, involving a total sample of 312 respondents. The findings indicate that performance expectancy, effort expectancy, price value, hedonic motivation, and trust positively influence behavioral intention. Meanwhile, the variables found to affect use behavior are facilitating conditions, habit, and behavioral intention. Furthermore, this study reveals that social influence does not have an effect on behavioral intention.